SOFTWARE PRODUCT INITIATIVE PRIORITIZATION WITH ANALYTIC HIERARCHY PROCESS IN DOCTOR TO DOCTOR APPLICATION - Agus, Arfian
Doctor to Doctor (D2D) is a mobile application for doctors that help doctors to upgrade their knowledge and service. In the face of competition, D2D needs to continuously innovate and improve its features to retain its users. Initiative ideas in D2D came from discussion with pharmaceutical companies, feedback from doctors, or ideas from D2D team. As the complexity and number of initiatives to be prioritized grows, the task becomes more complex and inconsistent, a model is required to evaluate conflicting criteria in an organized manner to ensure consistency and accuracy so that the decision that is achieved is coherent with the intuitionistic decision. The purpose of this research is to define the prioritization criteria and weighting system for criteria importance. This research utilized both qualitative and quantitative methodologies to gather information and identify criteria for prioritization. The primary data was gained from interviewing key decision makers in the company to understand the current prioritization process. Literature study and questionnaires were used to find the most prevalent prioritization method in the academic world and real-world practitioners. Another set of questionnaires were distributed to experts in the company to determine the weight of criteria using pairwise comparison. Lastly, experts in the company were interviewed to decide the rating of each sub-criteria for the alternatives. Three criteria and ten sub-criteria were identified to support the prioritization process using Analytical Hierarchy Process (AHP). The first criterion is demand with sub-criteria user demand, association demand, pharmaceutical company demand, and management demand. The second criterion is business sustainability with sub-criteria strategic fit, profitability margin, synergy, and competitive advantage. The last criterion is complexity which consist of technical complexity and operational complexity. The sub-criteria were then weighted using pairwise comparison and global weight of the sub-criteria were calculated. The sub-criteria with the highest global weight were competitive advantage, profitability margin, and user demand. To test the model, three initiatives were examined. These initiatives are Pairing TD, Webinar 360, and Multi-country. The quantitative rating of each alternative was multiplied with the global weight to obtain the final prioritization decision, resulting in Webinar 360 being the initiative with the highest priority.